Pengaruh Social Media Marketing terhadap Minat Beli dan Loyalitas Konsumen Kopi di Glas Macher Coffee Jakarta (Jurnal Agribisnis dan Agrowisata, 2025)
The Influence of Social Media Marketing on Buying Interest and Consumer Loyalty of Coffee at Glas Macher Coffee, Jakarta. Social media marketing is one of the marketing strategies in the digitalization era. This study aims to: 1) analyze the effect of social media marketing on the buying interest of coffee at Glas Macher Coffee Jakarta; 2) Analyzing the direct effect of social media marketing on consumer loyalty, as well as the indirect effect of social media marketing on consumer loyalty through mediation of interest in buying coffee at Glas Macher Coffee Jakarta. 3) Analyze the effect of purchase intention on consumer loyalty at Glas Macher Coffee Jakarta. This research was conducted at Glas Macher Coffee Jakarta from October to December 2022. The population in this study were followers of Glas Macher Coffee social media accounts, totaling 3,935 followers. The sample is determined based on the Slovin formula of 95 respondents. Data were analyzed using the Structural Equation Model (SEM) using the smartPLS 3.0 application. The results of the study show that: 1) Social media marketing has a positive and significant effect on consumer buying interest. This shows that increasing the quality and content of social media marketing will increase consumer demand to buy 2) Purchase intention has a positive and significant effect on consumer loyalty. Increasing consumer buying interest will increase consumer loyalty, 3) Social media marketing has a positive and significant effect on consumer loyalty. Social media marketing has a significant effect on consumer loyalty mediated by consumer buying interest.
Keywords: social media marketing; coffee shop; buying interest; consumers